2021
DOI: 10.1155/2021/8874827
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of a Weak Correlation between Complicated Data on the Basis of Principal Component Analysis

Abstract: The mining of weak correlation information between two data matrices with high complexity is a very challenging task. A new method named principal component analysis-based multiconfidence ellipse analysis (PCA/MCEA) was proposed in this study, which first applied a confidence ellipse to describe the difference and correlation of such information among different categories of objects/samples on the basis of PCA operation of a single targeted data. This helps to find the number of objects contained in the overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…4 A, blue squares), showing a decrease in the IGF2 levels and the expression of genes from the initial step of the autophagy pathway, excepting LC3B and RUBICON . Next, we evaluated the most predominantly variables (IGF2 and autophagy gene expression) associated with PD patients using a PCA, a statistical method that allows the association of the profile of gene expression for each patient 71 73 . For instance, we can find an association of patients' gender with a specific gene expression profile using this method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A, blue squares), showing a decrease in the IGF2 levels and the expression of genes from the initial step of the autophagy pathway, excepting LC3B and RUBICON . Next, we evaluated the most predominantly variables (IGF2 and autophagy gene expression) associated with PD patients using a PCA, a statistical method that allows the association of the profile of gene expression for each patient 71 73 . For instance, we can find an association of patients' gender with a specific gene expression profile using this method.…”
Section: Resultsmentioning
confidence: 99%
“…A heat map and a dendrogram analysis were performed using the GraphPad Prism 9 and Statistics 10.0 software to evaluate the potential clustering of patients and controls based on the expression levels of IGF2 and autophagy genes evaluated. To potentially categorize a predominant behavior for each patient based on the evaluated variables, IGF2 and autophagy genes expression, we performed a principal component analysis (PCA), a statistical method used to predict responses based on a group of multiple variables' information 71 73 using the Statistics 10.0 software 74 . mRNA expression levels in macrophage cell culture were analyzed using ordinary one-way ANOVA (parametric data).…”
Section: Methodsmentioning
confidence: 99%
“…According to the requirements of total eigenvalues (≥ 1) and cumulative variance (≥ 85%), only component 1 was extracted, that total eigenvalues and cumulative variance were 6.503 and 92.895%, respectively (Table 4). Loading values reflect the influence degree of indexes (Pang et al 2021). Table 5 showed that the two biggest loading values were TTA (0.982) and WLR (-0.982), which indicated TTA and WLR were two key factors to evaluate the quality of frozen sourdough.…”
Section: Resultsmentioning
confidence: 99%
“…4A, bottom), showing a decrease in the expression of genes from the initial step of the autophagy pathway, excepting LC3 and RUBICON. Then, we performed a principal component analysis (PCA) (Pang et al, 2021;Seki et al, 2019;Wang et al, 2021) by using the Statistics 10.0 software (Hair et al, 2013). This analysis revealed a clear separation pro le for a group of patients (PC1).…”
Section: Resultsmentioning
confidence: 99%